2020
DOI: 10.21203/rs.3.rs-130241/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of supplementation of inulin in dietary on lactation performance, rumen fermentation, ruminal microbial profile and metabolites in dairy cows

Abstract: Background Inulin is a kind of fructo-oligosaccharide (FOS) derived mainly from Jerusalem artichoke and chicory tubers, which is also a soluble dietary fiber. Inulin has become a scientifically proven prebiotic product with satisfactory effects in improving the structure of intestinal flora, regulating blood lipid and glycemia, etc., in humans and monogastric. However, unlike monogastric animals, ruminal microbes are the largest microbiota in ruminants. The microflora profile and metabolism activity in the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Chikwanha et al ( 40 ), who showed that polyphenol-rich grape pomace could improve rumen microbial diversity, evenness, and richness in lambs in in vitro fermentation experiments. Wang et al ( 41 ) demonstrated that supplementation of phenolic-rich inulin in the diet could increase the relative abundance of commensal microbiota in dairy cows. It was likely that the microorganisms could improve anthocyanin bioavailability in the gastrointestinal tract, enhancing the gut antioxidant capacity ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chikwanha et al ( 40 ), who showed that polyphenol-rich grape pomace could improve rumen microbial diversity, evenness, and richness in lambs in in vitro fermentation experiments. Wang et al ( 41 ) demonstrated that supplementation of phenolic-rich inulin in the diet could increase the relative abundance of commensal microbiota in dairy cows. It was likely that the microorganisms could improve anthocyanin bioavailability in the gastrointestinal tract, enhancing the gut antioxidant capacity ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adding inulin also increased propionate numerically. Wang et al (2020) showed that adding inulin to the feed of dairy cows increased net energy for lactation (NEl) leading to an increase in milk production. This is achieved by increasing the molar proportion of acetate, the ratio of acetate to propionate and by increasing the molar proportion of propionate in the rumen fluid of Holstein cows.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have reported an improvement in rumen fermentation and increased microbial protein synthesis (Wang et al, 2020(Wang et al, , 2021a and milk protein content upon inulin consumption (Xue et al, 2019). Erasmus et al (1992) reported that feed additives such as probiotics not only increase methionine flow, but also increase the flow of other amino acids into the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations